Optimización de la tecnología de producción de fideos fortificado con harina de Colocasia esculenta (Pituca) y pulpa de Mauritia flexuosa L.F (Aguaje) - Ramírez Alván, Nene Aurora (2025)
This work was to optimize the technology in the production of fortified noodles from Colocasia esculenta (pituca) flour and Mauritia flexuosa L.F (aguaje) pulp, the technological parameters were set for both drying time and formulation of the components, the pituca flour was dehydrated in a tray dryer at 55 ° C; the noodles were dried at temperatures 50 ° C, 55 ° C and 60 ° C for 120 minutes, in different proportions with pituca flour, wheat flour, aguaje pulp, aguaje oil at different amounts; the fortified noodles were subjected to sensory testing by students in food industries of the institution, being the formulation 90g wheat flour, 10g pituca flour, 25g aguaje pulp, 40g egg and 2ml of aguaje oil that gave the highest acceptability, with 54% indicating "I like it a lot", "I like it a little", "I like it extremely". Physicochemical analysis determined that said formulation contains the satisfactory result in: humidity 10.24%, protein 12.40%, ash 1.54%, fat 4.83%, pH 5.76, acidity 0.28%. In addition, they were microbiologically analyzed in order to confirm the existence of microbial contamination acquired in the process; responding as follows: Molds<10 cfu / g, total coliforms <3 nmp / g, staphylococcus aureus <10 cfu / g and salmonella sp. Absence in 25g. The microbiological analysis determined that it is safe and therefore suitable for human consumption.